Association of direct oral anticoagulant-proton pump inhibitor cotherapy with adverse outcomes: protocol for a population-based cohort study - Lehana Thabane; Lawrence Mbuagbaw; Michael Paterson; Laura Targownik; Mei Wang; Anne Holbrook; Deborah Siegal (BMJ Open)
Introduction Proton pump inhibitors (PPIs) are widely used for primary and secondary prevention of upper gastrointestinal bleeding. However, there remains controversy about the overall net clinical benefit of PPIs (omeprazole, rabeprazole, pantoprazole, lansoprazole) when coprescribed with direct oral anticoagulants (DOACs; dabigatran, rivaroxaban, apixaban, edoxaban). Our objective is to explore the risk of clinically relevant events, including bleeding, thromboembolic events and death, in patients prescribed DOACs while taking PPIs versus no PPI.Methods and analysis The protocol describes a retrospective cohort study of all Ontario residents aged 66 years or older with atrial fibrillation and at least one pharmacy dispensation for a DOAC identified using linked administrative healthcare databases covering 2009–2020. Ontario drug benefit dispensation records will be used to ascertain PPI exposure during DOAC therapy. The primary outcome is a composite of clinically relevant bleeding, thrombotic events or all-cause death. A minimum of 520 patients in total with at least one of the components of the composite outcome are needed. Poisson regression with a generalised estimating equation model will be used to calculate the adjusted incidence rate difference, incidence rate ratios 95% CI, adjusting for propensity for PPI use using inverse probability of treatment weights.Ethics and dissemination This research is exempt from REB review under section 45 of Ontario’s Personal Health Information Protection Act. We will report our findings in a peer-reviewed biomedical journal and present them at conferences. The study will provide useful evidence to optimise the coprescription of DOACs and PPIs in practice.